Center Variation in Intestinal Microbiota Prior to Late-Onset Sepsis in Preterm Infants. - Diana H Taft; Namasivayam Ambalavanan; Kurt R Schibler; Zhuoteng Yu; David S Newburg; Hitesh Deshmukh; Doyle V Ward; Ardythe L Morrow (PLoS ONE)
Objective Late onset sepsis (LOS) contributes to mortality and morbidity in preterm infants. We tested the hypotheses that microbes causing LOS originate from the gut, and that distortions in the gut microbial community increases subsequent risk of LOS. Study design We examined the gut microbial community in prospectively collected stool samples from preterm infants with LOS and an equal number of age-matched controls at two sites (Cincinnati, OH and Birmingham, AL), by sequencing the bacterial 16S rDNA. We confirmed our findings in a subset of infants by whole genome shotgun sequencing, and analyzed the data using R and LEfSe. Results Infants with LOS in Cincinnati, as compared to controls, had less abundant Actinobacteria in the first samples after birth (median 18 days before sepsis onset), and less abundant Pseudomonadales in the last samples collected prior to LOS (median 8 days before sepsis onset). Infants with LOS in Birmingham, as compared to controls, had no differences identified in the first sample microbial communities, but Lactobacillales was less abundant in the last samples prior to LOS (median 4 days before sepsis onset). Sequencing identified detectable levels of the sepsis-causative organism in stool samples prior to disease onset for 82% of LOS cases. Conclusions Translocation of gut microbes may account for the majority of LOS cases. Distortions in the fecal microbiota occur prior to LOS, but the form of distortion depends on timing and site. The microbial composition of fecal samples does not predict LOS onset in a generalizable fashion.